PENEGAKAN HUKUM DALAM PROSES PERKARA PIDANA ABORTUS PROVOKATUS KRIMINALIS OLEH KEPOLISIAN REPUBLIK INDONESIA - Wibisana, Tezar Indra (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACT There is a difference in behavior between rural and urban societies, in which this distinction concerns the social order even to crime. Crime in big cities is more diverse as murder, crimes against decency include sexs, as well as frequent provocate abortion. Crimes such as abortus provokatus, does not mean not in small towns or in villages, it's just the methods and nature of crime are also different percentages. In the great cities of intercourse between the teenagers already so free, it is easier to accept foreign cultures without being filtered first and negative, so that religious, ethical and moral norms appear blurred, while in small towns or in villages some people still see if talking about the issue of sexs and / or decency, it is a small part to distinguish the evil abortion provokatus that occurred in the village and city. So the abortion provokatus that occurs in the village and town, both the nature and the method there is little difference. Abortus provokatus is not only criminal, but also medicinalist. But in society or social reality because in our country laws and laws still prohibit the existence of abortus provokatus, then abortion provokatus criminal is common. Abortion provokatus criminal and abortion provokatus medicalinalis not a youth group, but also the old group who already have many children and little children. Parents who are still able to bear children but pregnancy is not desired because of economic factors, health and so forth. Can also occur by parents who are married or young, because the relationship is also because of the consequences of raped and so forth.Â Keywords: Abortus Provokatus, Criminalist